Pattern, Treatment and Outcomes of Children with Head Injuries: A 3 Year experience from a TC Hospital of South Punjab, Pakistan - Shakeel Ahmed, Malik Liaqat Ali Jalal, Shoaib Saleem Khan, Ikramullah Akhter, Muhammad Rizwan, Waqas Noor Chughtai (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine pattern, treatment and outcomes of children with head injury. Study Design: A retrospective study. Place and Duration of the Study: Department of Pediatric Neurosurgery, The Children’s Hospital and Institute of Child Health, Multan Pakistan from January 2019 to December 2021. Material and Methods: A total of 1285 children of both genders aged up to 12 years with head injury were included. Patients were initially presented in emergency department while initial assessment along with physical examination was performed in emergency department among all children. Relevant radiological investigations were performed in all cases as per supervision of the senior consultant surgeon on duty. Demographic data along with pattern, treatment and outcome of children with head injury was noted. Results: In a total of 1285 children, 822 (64.0%) were male and 463 (36.0%) female. Mean age at the time of presentation was 4.7±2.5 years. Area of residence was urban in 1051 (81.8%) children while 234 (18.2%) belonged to rural areas of residence. Most common reason behind head injury was fall shown in 757 (58.9%) children whereas road-traffic accidents accounted for 414 (32.2%) children. Diffuse axonal injury was the most common head injury noted in 778 (60.5%) followed by linear fractures 152 (11.8%). Crainiotomy and bone elevation were performed in 54 (4.2%) and 117 (9.1%) children respectively while remaining 1114 (86.7%) children were treated conservatively. Mortality was noted in 25 (1.9%) children. Conclusion: Falls followed by road-traffic accidents were the most common mode of head injury among children. Diffuse axonal injury accounted for nearly 2/3rd of all head injury cases. Large majority of the children were treated conservatively while overall outcomes were good among children with head injury.